2018
DOI: 10.1164/rccm.201709-1917oc
|View full text |Cite
|
Sign up to set email alerts
|

Positive End-Expiratory Pressure Ventilation Induces Longitudinal Atrophy in Diaphragm Fibers

Abstract: Mechanical ventilation with PEEP results in longitudinal atrophy of diaphragm fibers, a response that is modulated by the elasticity of the giant sarcomeric protein titin. We postulate that longitudinal atrophy, in concert with the aforementioned cross-sectional atrophy, hampers spontaneous breathing trials in critically ill patients: during these efforts, end-expiratory lung volume is reduced, and the shortened diaphragm fibers are stretched to excessive sarcomere lengths. At these lengths, muscle fibers gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
71
0
5

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(87 citation statements)
references
References 50 publications
(56 reference statements)
11
71
0
5
Order By: Relevance
“…A decrease in Tdi was shown to be associated with longer periods of mechanical ventilation, and it occurs early after intubation [2,25]. The higher levels of PEEP in patients with diaphragm thinning during CMV could be in line with the recent evidences regarding myofibre longitudinal atrophy due to PEEP [6]. To our knowledge, no studies until now described the relation between the prealbumin levels, as an index of nutritional status [17], and diaphragm thickness.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…A decrease in Tdi was shown to be associated with longer periods of mechanical ventilation, and it occurs early after intubation [2,25]. The higher levels of PEEP in patients with diaphragm thinning during CMV could be in line with the recent evidences regarding myofibre longitudinal atrophy due to PEEP [6]. To our knowledge, no studies until now described the relation between the prealbumin levels, as an index of nutritional status [17], and diaphragm thickness.…”
Section: Discussionsupporting
confidence: 64%
“…Ultrasound (US) is becoming a reference to assess diaphragmatic injury and to detect changes in diaphragmatic thickness over time; both an increase and a decrease of diaphragmatic thickness are associated with diaphragm activity and ventilation outcome [1,2]. Starting from experimental and clinical studies, four mechanisms of diaphragmatic injury (myotrauma) have been identified: disuse atrophy due to over-assistance [3], excessive load due to under-assistance [1,4], eccentric myotrauma from diaphragm contraction during expiration [5] or asynchronies, and longitudinal atrophy, due to high level of positive end-expiratory pressure (PEEP) [6]. Therefore, the need to set "protective" mechanical ventilation not only for the lungs but also for the diaphragm was recently advocated [7].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, preliminary experimental evidence suggests that if the diaphragm is maintained at a shorter length during acute mechanical ventilation, the diaphragm muscle fibers could adapt to the reduced length by absorbing sarcomeres in series (i.e., longitudinal atrophy) [ 52 ]. This may result in fibers overstretching with the release of PEEP during a T-tube weaning trial or after extubation.…”
Section: Clinical Strategies To Facilitate Lung and Diaphragm-protectmentioning
confidence: 99%
“…Excessive PEEP. Preliminary experimental evidence suggests that maintaining the diaphragm at a shorter length with the use of excessive PEEP may cause sarcomeres to "drop out" of the muscle and shorten its length (longitudinal atrophy) [18]. This could theoretically disadvantage the length-tension characteristics of the muscle once PEEP is reduced, impairing diaphragm performance.…”
Section: Diaphragm Injury During Spontaneous Breathing: Myotraumamentioning
confidence: 99%